Pluralism Out Of The Sources Of Judaism: Religious Pluralism Without Relativism - Jospe, Raphael (Studies in Christian-Jewish Relations, 2011)
Jewish theology is compatible with religious pluralism, based on the paradigm of the Jewish obligation to live in accordance with the commandments of the Torah while accepting the legitimacy of other ways of life in accordance with the paradigm of the universal “seven commandments of the children of Noah.” Jospe here answers two challenges to this thesis, one, voiced by Christian theologians, that pluralism equals relativism, and a second, voiced by the Jewish scholar, Menachem Kellner, that there are no sources for pluralism in Jewish tradition and that pluralism itself makes no sense. In presenting his arguments, Jospe invokes a wide range of ancient, medieval and modern thinkers, probing the theological possibilities for pluralism within Jewish tradition and its boundaries with relativism. In doing so, he argues that one should differentiate between moral relativism, a non-negotiable category, and epistemological relativism, where there is room for compromise.